2021
DOI: 10.1038/s41598-021-98070-0
|View full text |Cite
|
Sign up to set email alerts
|

Daily activity in minimal footwear increases foot strength

Abstract: The human foot is uniquely adapted to bipedal locomotion and has a deformable arch of variable stiffness. Intrinsic foot muscles regulate arch deformation, making them important for foot function. In this study we explore the hypothesis that normal daily activity in minimal footwear, which provides little or no support, increases foot muscle strength. Western adults wore minimal footwear for a six-month period (the “intervention” group). Foot strength, i.e., maximum isometric plantarflexion strength at the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 50 publications
1
22
1
Order By: Relevance
“…The four studies that assessed toe flexion strength used three different custom dynamometers 1 30 31 35 . Quinlan et al (2022) did not find a correlation between muscle size (CSA) and strength (hand-held dynamometer) in children, which opposes findings in adult populations 35 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The four studies that assessed toe flexion strength used three different custom dynamometers 1 30 31 35 . Quinlan et al (2022) did not find a correlation between muscle size (CSA) and strength (hand-held dynamometer) in children, which opposes findings in adult populations 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated that habitually barefoot individuals have fewer foot and toe deformities and defects [27] as well as higher arch heights [28,29] compared to conventionally shod runners. Similarly, some individual studies have reported statistically significant improvements in IFM strength [1,30,31] and size [14,17,31,32] due to the usage of minimalist shoes. However, a systematic review to understand these changes in IFM strength or size has not yet been performed.…”
Section: The Effects Of Minimalist Shoes On Plantar Intrinsic Foot Mu...mentioning
confidence: 91%
See 3 more Smart Citations